Modifying the Stability and Surface Characteristic of Anthocyanin Compounds Incorporated in the Nanoliposome by Chitosan Biopolymer - Mina Homayoonfal; Mohammad Mousavi; Hossein Kiani; Gholamreza Askari; Stephane Desobry; Elmira Arab-Tehrany (MDPI AG, 2022)
In this study, a novel approach was investigated to improve the stability of anthocyanin compounds (AC) by encapsulating them in nanoliposomes resulting from rapeseed lecithin alongside chitosan coating. The results indicate that the particle size, electrophoretic mobility, encapsulation efficiency, and membrane fluidity of nanoliposomes containing anthocyanin compounds were 132.41 nm, −3.26 µm·cm/V·S, 42.57%, and 3.41, respectively, which changed into 188.95 nm, +4.80 µm·cm/V·S, 61.15%, and 2.39 after coating with chitosan, respectively. The results also suggest improved physical and chemical stability of nanoliposomes after coating with chitosan. TEM images demonstrate the produced particles were spherical and had a nanoscale, where the existence of a chitosan layer around the nanoparticles was visible. Shear rheological tests illustrate that the flow behavior of nanoliposomes was altered from Newtonian to shear thinning following chitosan incorporation. Further, chitosan diminished the surface area of the hysteresis loop (thixotropic behavior). The oscillatory rheological tests also show the presence of chitosan led to the improved mechanical stability of nanoliposomes. The results of the present study demonstrate that chitosan coating remarkably improved encapsulation efficiency, as well as the physical and mechanical stability of nanoliposomes. Thus, coating AC-nanoliposomes with chitosan is a promising approach for effective loading of AC and enhancing their stability to apply in the pharmaceutic and food industries.